Ref-Litpsy Module: A Literacy-Psychospiritual Module For Refugees - Hazlina Abdullah; Dini Farhana Baharudin; Hazleena Baharun; Fariza Puteh Behak; Noor Saazai Mat Saad; Mohd Zaliridzal Zakaria; Rodziana Mohamed Razali; Suraini Mohd Ali; Habibah Ismail (Human Resource Management Academic Research Societ, 2024)
Indexed by ERA